2014
DOI: 10.1007/s11869-014-0272-9
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of inter-seasonal differences in NO2 concentrations using a dispersion ADMS-Urban model and measurements

Abstract: Air pollution dispersion modeling is one of the methods for the ambient air quality assessment. The mathematical models are widely used tools for predicting air pollution and accurately assessing the spatial distribution of air pollutants in the city. Road transport is one of the main sources of pollution affecting air quality in urban areas, and nitrogen dioxide is considered to be one of the most common with traffic emission-related pollutant, which concentrations are strongly correlated to the distance from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Another study was performed to check the reliability of the numerical model results, focusing on the estimation of average annual NO 2 concentration near heavy traffic streets in the city of Kaunas in Lithuania. The modelled results have obtained a plausible correlation of 75% with the observed concentration in summer and winter [12].…”
Section: Introductionsupporting
confidence: 55%
“…Another study was performed to check the reliability of the numerical model results, focusing on the estimation of average annual NO 2 concentration near heavy traffic streets in the city of Kaunas in Lithuania. The modelled results have obtained a plausible correlation of 75% with the observed concentration in summer and winter [12].…”
Section: Introductionsupporting
confidence: 55%
“…The results showed that the model underestimated NO x and NO 2 concentrations but that R 2 equaled 0.88. Dėdelė and Miškinytė ( 37 ) used ADMS-Urban to model NO 2 concentrations in Kaunas city and validated the modeled concentration against measurements from 41 Ogawa passives samplers operated as part of ESCAPE. Differently from the other studies, the vehicle fleet was assigned an age of 14 years to calculate emissions.…”
Section: Discussionmentioning
confidence: 99%
“…It considers the processes of gravity settlement, building topography and chemical reactions, then simulates multiple traffic pollution sources with different spatial distributions and finally obtains a higher-resolution pollutant concentration map to analyze the impact of different pollution sources on the prediction results [ 22 ]. It can accurately simulate not only the diffusion of pollutants emitted by various pollution sources in the atmosphere, including point, line and surface sources, but also their impact on the environment [ 23 , 24 , 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%